2016
DOI: 10.1158/1078-0432.ccr-15-1543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PD-L1 Expression and Associated Tumor-Infiltrating Lymphocytes in Laryngeal Squamous Cell Carcinoma

Abstract: Purpose: Programmed death-ligand 1 (PD-L1; also known as CD274 or B7-H1) expression represents a mechanism of immune escape for cancer. Our purpose was to characterize tumor PD-L1 expression and associated T-cell infiltration in primary laryngeal squamous cell carcinomas (SCC). Experimental Design: A well-annotated cohort of 260 operable primary laryngeal SCCs [formalin-fixed paraffin-embedded (FFPE) specimens] was morphologically characterized for stromal tumor-infiltrating lymphocytes (TIL), o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
6
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(179 citation statements)
references
References 34 publications
11
158
6
4
Order By: Relevance
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, PD-L1 expression was correlated with improved survival in laryngeal squamous cell carcinomas (17). In another study, PD-L1 expression did not demonstrate an overall survival benefit in patients with cervical cancer (N=115 patients) (18).…”
Section: Resultsmentioning
confidence: 99%
“…Similar favorable findings were seen with increased intra-tumoral or stromal CD8 + cells [240], while increased numbers of FOXP3 + T regs may have detrimental effects oral cavity squamous cell carcinoma outcome [241]. Vassilakopoulou et al and Wang et al applied the consensus TILs scoring guidelines from the International Immuno-Oncology Biomarkers Working Group [1] to laryngeal squamous cell carcinoma, and both studies found that the sTILs score was an independent prognostic factor for disease free and overall survival [242,243]. …”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%